Influence of various impact scenarios on the dynamic performance of concrete beam-column joints - Huawei Li; Wensu Chen; Zhijie Huang; Hong Hao; Tuan T. Ngo; Thong M. Pham (My University, 2022)
Influence of various impact scenarios on the dynamic performance of concrete beam-column joints
Keywords: Va chạm động; Mối nối dầm-cột; Phản ứng động lực học